Analisis Daya Saing Industri Pengolahan Kakao Indonesia - Clara Dwi Purnama Sari; Bernadette Robiani; Mukhlis , Mukhlis; Muhammad Teguh (Edunomics Journal, 2024)
This study aims to see how the competitiveness of the cocoa processing industry in Indonesia, where the main raw material is cocoa which is one of Indonesia's leading commodities and is processed into several products through Indonesia's growing cocoa processing industry. This study compares the competitiveness of the cocoa processing industry in Indonesia with Côte d'Ivoire, Ghana, Nigeria and Brazil, which are the largest cocoa producers and processors in the world. This study provides an overview of the position of the Indonesian processing industry in the global market. The data in this study are sourced from the Central Bureau of Statistics, International Cocoa Organization, UN COMTRADE, Ministry of Industry, and Ministry of Trade of the Republic of Indonesia. To measure competitiveness, the Revealed Comparative Advantage (RCA) method was used using export data from five countries for the period 2015-2022. The results showed that Indonesia's RCA value was 9.12 and the country was in third position among the five countries. This means that the cocoa processing industry in Indonesia must be improved given its high cocoa production.